¿Musulmán o judío? La imagen interconectada del «otro» en la Corona de Aragón (ca. 1390-ca. 1450) - Francesc Granell Sales (Mélanges de la Casa de Velázquez, 2024)
The historiography on religious otherness in art has analysed separately the Muslim signs and those of the Jew, as if this differentiation was due to an iconographical classification already conceived by medieval societies. However, it is known that certain artworks cannot adapt to an epistemological framework created by a taxonomy of figurative production. This paper selects a significant group of images that combine equally Muslim and Jewish symbols in order to look at the visual interrelation proposed between these two cultures. It frames the images in their own historical context and it analyses them as a projection of interreligious coexistence in the four main realms which belonged to the Crown of Aragon between 1390 and 1450.